Would bond market be more viable investment alternative to the stock market? / Nor Farradila Abdul Aziz, Maizura Mohd Isa @ Kamaruddin and Mohd Khalimi Ashraf Mohamed Rethuan - Abdul Aziz, Nor Farradila; Mohd Isa @ Kamaruddin, Maizura; Mohamed Rethuan, Mohd Khalimi Ashraf (2012)
This paper investigates the co-movement of stocks and bonds on a monthly basis for the period of Jan 1998 until Dec 2008. Average returns and standard deviations for both bond and stock market are computed and comparison is performed to determine which market provides a better return, less volatile and high liquid especially during stress events. The finding indicates that the bond market on the average has outperformed the stock market during the period of the study especially during stress events. Furthermore, bond market seems to be more stable instrument indicated by lower volatility vis-à-vis stock as well as more liquid instruments as indicated by high volumes. The low interest rate regime as a result of interest rate cuts further increases bond yields and makes them a safer and more attractive investment as compared to stock. The study concludes that bond market can become more viable investment alternative than the stock market. In addition, the government plan to liberalise the bond market by allowing lower rating to be traded could spur more interest. The bond market also is expected to expand the issuance of securitisation base investment product which likely to offer yield enhancement hence, making bond market more attractive.